Sustainability Comparison for Steel and Basalt Fiber Reinforcement, Landfills, Leachate Reservoirs and Multi-Functional Structure - Adejuyigbe, IfeOluwa B.; Chiadighikaobi, Paschal C.; Okpara, Donatus A. (Civil Engineering Journal, 2019)
To a large extend sustainable construction of any structure greatly depends on the materials used in its formation. Traditionally, materials such as bricks, mortar, steels are still important components of most buildings. But modern technology is equally changing how materials are created and used.Based on the above explanation, the objective of this paper was to compare the steel structures with basalt fiber reinforced concrete. As basalt fiber is still not wide spread, this paper focus on the advantages, usages and applications of basalt fiber reinforced concrete to solve construction and structural challenges. The method and analysis used in this paper was derived from research and works done by previous authors on similar topics. Previous research information show that producers and users of these materials make choice of building materials to depend on the area the structure is proposed to be built and on the taste and ideas given by the client. Their consideration is often devoid of environmental, psychological, social and economy factors. The research methods lead to the understanding on the use and importance of basalt fiber concrete for landfills, leachate reservoirs and multifunctional structure.This paper helps structural users and engineers to know that green materials with good environmental characteristics that support nature are being considered as best construction materials due to what they are composed of. Waste and cost are also crucial as far as construction materials are concern. Even now, management of waste products from landfills specially leachates requires better construction designs in tropical region like Nigeria. More so, in line with the recent safe the climate calls, efforts to select the kind of material used in raising structures are becoming unavoidable.